MENINGKATKAN KECERDASAN KINESTETIK ANAK MELALUI GERAK TARI HUDOQ DAYAK BAHAU DI TAMAN KANAK –KANAK NEGERI PEMBINA 2 MUARA WAHAU - Yanti, Nila Sari; Hanita, Hanita (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2020)
A child is defined as an individual who entering adult phase. When they are getting older, they must master basic competence. In this stage, all potentials they have are developed, including kinesthetic intelligence. In case of students in Pembina 2 Kindergarten Muara Wahau, they showed low kinesthetic intelligence since they looked bored, and did not focus on lesson when doing sport exercise. Kinesthetic intelligence in early age students can be stimulated through dance, since, basically, they like music and dance. Dancing demands balance, body movement coordination, strength, and muscle flexibility. This study applied classroom action research. The research subjects were students of Group B Pembina 2 Kindergarten Muara Wahau. Meanwhile, the aspects being analyzed were students? ability in imitating the movement fast, remembering dance movement, coordinating movement and rhythm, and dancing without help. The data were collected through documentation and direct observation toward the teacher and the students, observing teacher conducting teaching and learning process by implementing Hudoq Dayak Bahau dance. The result shows that, in pre-cycle, the average score was 17,3%, meaning that students had not developed yet. At the first cycle, students achieved 40,98%, meaning that students started to develop. The percentage increased into 97,7% at second cycle, meaning that students developed very well. Therefore, it can be concluded that teaching with Hudoq dayak bahau dance is effective to improve kinesthetic intelligence, especially for students of group B in Pembina 2 Kindergarten Muara Wahau. It is expected that teachers can apply this method to improve students? kinesthetic intelligence.